On the investigation of bridge buffeting simulation techniques - Liu, Zhe (2012)
The buffeting response is a type of vibration caused by wind turbulence. As the bridge span and structural complexity increase, this kind of response is notable. Therefore more accurate analysis simulation methods are needed to investigate this aerodynamic phenomenon. The aim of this thesis is to review, discuss and compare the different bridge buffeting simulation approaches in the frequency domain and find the possibility of Computational Fluid Dynamic (CFD) method application in bridge buffeting prediction. In this thesis, the conventional bridge buffeting statistical analysis methods considering the influence of different parameters such as mode coupling, self-excited forces and aerodynamic admittance on the simulation results are firstly reviewed and compared. Since wind turbulence may not excite all structural vibration modes in some frequency ranges, an alternative approach based on the Proper Orthogonal Decomposition (POD) is proposed to study the effective turbulence contribution to the structural vibration. However due to the complexity of turbulence, quasi-steady theory is widely adopted and some semi-empirical functions such as aerodynamic admittance, joint acceptance are introduced to simplify the simulation. With the development of CFD method, CFD simulation of bridge aerodynamic phenomena has become possible. Since the bridge buffeting response is induced by wind turbulence, it is very important to capture the time varying characteristics of wind turbulence. In CFD technique, to close the Navier-Stokes equations and reflect unsteady characteristics, turbulence modelling is always adopted. At present Direct Numerical Simulation (DNS) is an accurate model to capture the time variation unsteady characteristic of the wind turbulence. However, the problems of civil engineering are always high Reynolds numbers, which make the simulation of aerodynamic phenomena of civil engineering impractical based on DNS method. Therefore an alternative model, known as Large Eddy Simulation (LES), becomes popular. In this thesis an unsteady inlet boundary generation technique based on an Autoregressive Moving Average (ARMA) model is proposed to simulate the unsteady inflow turbulence. 3D LES will be selected to validate the applicability of this model in the prediction of the unsteady characteristic of buffeting simulation by investigating the flow characteristic around a square cylinder under different mesh density and different LES model such as standard LES model, dynamic LES model and WALE model at Reynolds number 13,000. Before comparing the influence of inflow boundary condition with turbulence intensity (5%) on the flow around a square cylinder, an empty domain is selected to validate current inflow turbulence generation technique. Major steps of Fluid Structure Interaction (FSI), suitable for future simulation of bridge structural buffeting response, are proposed to predict the structural buffeting response induced by the inflow turbulence. To test the propose procedure of FSI, a square cylinder will be used, the across-flow oscillation of square cylinder with constant damping ratio will be considered to investigate the influence of steady inlet boundary condition and unsteady one on the response of structure. In addition different LES models are considered to compare their influence on the response of square cylinder.